The Hum of the Turbine, the Roar of the Crowd Millicent Hodson's reconstrucion of Le Pas d'Acier - Siegel, Marcia B. (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Millicent Hodson and Kenneth Archer stage Le Pas d'Acier at Princeton. PALABRAS CLAVE: Millicent Hodson, Kenneth Archer, Le Pas d'Acier, The Steel Step, Diaghilev, Princeton Univesity.